Evaluasi Kualitas Website SMK Negeri 1 Lhoknga Metode Webqual 4.0 - Wulandari, Yuli; Anita, Anita; Puspitasari, Ni Luh Gede Dian; Ramadiani, Ramadiani (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The rapid advancement of information and communication technology has encouraged educational institutions to optimize their digital platforms, particularly school websites, to support academic and administrative activities. However, ensuring that these websites meet the needs and expectations of their users requires regular evaluation. This study aims to assess the quality of the SMK Negeri 1 Lhoknga website using the Webqual 4.0 method, which evaluates three main dimensions: usability, information quality, and service interaction quality. A descriptive quantitative approach was employed through a survey involving 61 active users, including students, teachers, and administrative staff, selected using purposive sampling. Data were collected via an online questionnaire based on the Webqual 4.0 indicators, utilizing a five-point Likert scale, and analyzed using descriptive statistics. The findings show that all three dimensions are categorized as “good,” with service interaction quality scoring the highest (3.81), followed by usability (3.79) and information quality (3.78). The dominant factor influencing user satisfaction was service interaction quality, highlighting the importance of system stability, accessibility, and security. Recommendations include regularly updating content, implementing a more modern and responsive design, and adding interactive features such as live chat and digital suggestion boxes to enhance user experience. These results provide practical insights for improving the school’s digital services and contribute to the broader discussion on educational website quality assessment.